SISTEM PEMBAYARAN KLAIM ASURANSI KENDARAAN BERMOTOR PADA PT. JASARAHARJA PUTERA CABANG BENGKULU MENGGUNAKAN BAHASA PEMROGRAMAN VISUAL BASIC 6.0 - Ade Tri Wijaya; Asnawati Asnawati (UNIVED Press, 2014)
The objective of this research is to develop the information system for motor vehicle insurance claims payment at PT. Jasaraharja Putra Branch Bengkulu so as to help speed up the search process in the payment of motor vehicle insurance claims. The method used is a method in which a new system of payment systems in the motor vehicle insurance claims PT. Jasaraharja Putera Branch Bengkulu, is still conducted manually data that is stored in softcopy and hardcopy. Analysis and design systems visually depicted using Visual Basic 6.0 programming language as the language. Results of anlisis and design of this system, is expected to enhance the insurance information system is running by reducing the weaknesses that had been there, and can help speed up the employees in the search data. Suggestions of the author with the information system of payment of these claims can Implement effective and efficient so as to produce a good performance.Keywords: Information System for Motor Vehicle Insurance Claims